Diffusion of an interdiscipline : social sciences in agriculture education - Singh, Yogendra Pal, 1936- (Published by New Heights for Indian Society of Extension Education : stockists and distributors, Rainbow Book Co., 1974)
On higher agricultural education in India; includes a comprehensive bibliography of master's and doctoral dissertations on agriculture submitted to institutions in India.